2015
DOI: 10.26719/2015.21.5.309
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to antihypertensive medication in northern United Arab Emirates

Abstract: This study aimed to assess the predictors of non-adherence to antihypertensive medications in northern United Arab Emirates. In a cross-sectional, multicentre study in Ajman Emirate, 250 patients with hypertension were randomly selected from outpatient clinics. Participants answered an interview questionnaire about sociodemographic and clinical data and completed the Morisky medication adherence scale. Non-adherence to antihypertensive medication was reported by 45.6% of patients. Sociodemographic predictors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
25
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 27 publications
15
25
4
3
Order By: Relevance
“…In United Arab Emirates [32], adherence to antihypertensive medication(s) was reported to be 54.4% which is lower than our finding. This may be attributed to the presence of comorbidities and advanced age of the patients which may significantly affect medication adherence.…”
Section: Discussioncontrasting
confidence: 97%
“…In United Arab Emirates [32], adherence to antihypertensive medication(s) was reported to be 54.4% which is lower than our finding. This may be attributed to the presence of comorbidities and advanced age of the patients which may significantly affect medication adherence.…”
Section: Discussioncontrasting
confidence: 97%
“…Participants in the current research revealed nonadherence rate of 81%. Our finding is consistent with previous research findings, and it is relatively higher than what has been reported in other studies . Most of the recent studies which assessed medication nonadherence rates in the Middle East area reported better adherence rates (23–49.5%) .…”
Section: Discussionsupporting
confidence: 93%
“…[27,28] In contrast to our findings, other studies have reported adherence to be higher among people above 60 years of age and females. [23,29] In this study, good adherence was found to be associated with higher level of education and employment in a skilled occupation which may be due to better knowledge about the disease and its treatment. Similar results were obtained in a study done in Iran as well as in India.…”
Section: Discussionmentioning
confidence: 88%
“…[18,25] Good adherence was observed in patients who were on monotherapy, 70.5%, than those on polytherapy, 29.5%, and also among those on once a day prescription, 53.8%, which is similar to the results obtained in various studies done all over the world. [18,23,25,29] This suggests the importance of keeping the prescription of antihypertensive drugs and its dosing to a minimum to improve the treatment compliance. In another study done in North India regarding prescription practices for antihypertensive drugs, it was observed that monotherapy (81.7%) with calcium channel blockers was more common than combination therapy (34.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation